Power Quality in the Context of Aircraft Operational Safety - Tomasz Tokarski; Sławomir Michalak; Barbara Kaczmarek; Mariusz Zieja; Tomasz Polus (Energies)
The article presents the use of ground power sources for aircraft ground support. Both military and civil aircraft (A/C) require high-performance and reliable Ground Power Units (GPUs) to ensure safe operation in diverse environmental conditions. The power quality provided by these GPUs plays a crucial role in determining the reliability, cost efficiency and operational safety of the aircraft. The main objective of the article is to signal and propose a solution to the problems associated with the operation of GPUs in the Polish Armed Forces (PAF), resulting from the diversity of the equipment used (type, duration of operation, defects occurrence, etc.). Currently, the PAF utilize various types of GPUs to provide electrical power to aircraft while they are on the ground. Many of those devices have already been in service for many years. The presented statistics of defects registered in the airworthiness management system showed several dozen A/C failures or defects related to the operation of GPU. The authors highlight the importance and feasibility of diagnosing these ground-based power sources. The presented sample test results confirm that, following the methodology outlined in the article, it is possible to conduct comprehensive diagnostic assessment of the GPU systems currently in use by the PAF, as well as evaluate the quality of the electrical power they deliver in both steady and transient states.